Fratture periprotesiche: la revisione del ginocchio in acuto - Benazzo, F.; Ghiara, M.; Rossi, S.M.P. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FRACTURE—ACUTE KNEE REVISIONPeriprosthetic fractures are an increasingly common complication following total knee arthroplasty, especially ingeriatric patients. Supracondylar fracture is the most frequent type and it is often linked to femoral notching. Thecorrect classification of the fracture prompts the surgical decision; however, the loosening of a prosthetic implant needsrevision surgery in the acute setting. The purpose of the treatment includes bone defect reconstruction and thestability of the implant, to allow for immediate weight-bearing and fast patient rehabilitation.